COMPREHENSIVE ANALYSIS OF CATHETER-ASSOCIATED URINARY TRACT INFECTIONS: RISK FACTORS, MICROBIAL DYNAMICS, AND ANTIMICROBIAL CHALLENGES IN A TERTIARY CARE SETTING - JADHAV, RAVIKUMAR; NG, THAKAPPA; RAYKAR, RAVIRAJ; GB, MANJUPRASAD; SAMPATHKUMAR; Mahadik, Shivaratna; RATKAL, JAIDEEP (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Our objectives included investigating CAUTI incidence, exploring factors contributing to UTI risk, examining the correlation between bacteriuria and symptomatic CAUTI, and recording microbiological profiles and antibiotic sensitivities for insights into microbial dynamics and treatment strategies. Indwelling urinary catheters are frequently employed in medical procedures; yet, they pose a considerable risk, with catheter-associated urinary tract infections (CAUTIs) being a global healthcare challenge. CAUTIs account for 30–40% of nosocomial infections, contributing to heightened morbidity and mortality. Method: We aimed to assess patient and catheter-related factors influencing urinary tract infections (UTIs) in 105 catheterized patients. Results: Among the studied cohort, with an average age of 47.73 years, various catheter sizes were employed, and post-operative catheterization was the predominant indication. Microbial presence in urine samples was detected in 31.4% of cases, with a 21% prevalence of symptomatic UTIs. Diabetes mellitus showed a significant association with increased UTI occurrences (p=0.019). Notably, catheterization outside the operating theater (OT) and prolonged catheterization duration were significantly associated with increased infection rates (p=0.000 and p=0.003, respectively). Despite antibiotic treatment, Escherichia coli remained the most prevalent organism causing infection (17.1%), and antibiotic resistance trends were observed, highlighting the challenges of antimicrobial stewardship. Conclusion: The study emphasizes the importance of preventive measures, such as reducing catheterization duration and meticulous diabetes management, to mitigate the burden of CAUTIs. In conclusion, this study provides valuable insights into the prevalence, risk factors, and microbial dynamics of CAUTIs, urging a shift toward proactive prevention strategies and judicious antibiotic use to enhance patient outcomes and alleviate the strain on health-care resources.